A kinetic approach on the effect of Cs addition on oxygen reduction for MCFC application. (1st December 2015) - Meléndez-Ceballos, A.; Albin, V.; Lair, V.; Ringuedé, A.; Cassir, M.
Abstract: Optimization of the molten carbonate electrolyte is the most challenging topic in order to increase the lifetime and performance of the molten carbonate fuel cell (MCFC). Besides controlling electrolyte properties such as stability, conductivity, volatility, surface tension, molar volumes etc., it is mandatory to reduce the dissolution of the Lix Ni1−x O state-of-the-art cathode. Furthermore, the nature of the eutectic also may influence the electrode kinetics and, in particular, at the cathode side where the reduction reaction is known to be slow. The conventional molten salt used in MCFC devices is composed by Li2 CO3 –K2 CO3 (62/38 mol%), which has a better performance at temperatures below 600 °C than Li2 CO3 /Na2 CO3 (52/48 mol%) electrolyte but presents a higher Ni solubility than the Li–Na electrolyte. To improve the properties of the Li–K eutectics towards the ORR (oxygen reduction reaction), heavy alkali cations such as Cs or Rb can be used as additives in the electrolyte. The present work is dedicated to a thorough analysis of the oxygen reduction kinetics in Li2 CO3 –K2 CO3 (62/38 mol%) eutectic containing small amounts of Cs2 CO3 by means of impedance spectroscopy and fitting performed using Warburg and Gerischer models, showing the favourable effect of this additive and convenience between the two model approaches.